2014
DOI: 10.1210/jc.2013-4409
|View full text |Cite
|
Sign up to set email alerts
|

IL-34 Is Associated with Obesity, Chronic Inflammation, and Insulin Resistance

Abstract: The present study demonstrates, for the first time, that IL-34 is expressed in human adipose tissues and the circulating concentration is significantly elevated in obese patients. This suggests that IL-34 is associated with insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 36 publications
1
83
0
1
Order By: Relevance
“…The results showed that the mean IL-34 levels in GCF (969.44±143.27 pg/ml) and plasma (774.02±215.47) were increased in patients who were obese and had periodontitis (Group IV) compared to in the other groups, and this difference was statistically significant (p<0.001). Chang et al also found IL-34 expression in human adipose tissue, and the circulating concentration was significantly elevated in obese patients and was associated with insulin resistance 7) . Zorena et al concluded that IL-34 could serve as an additional potential inflammatory biomarker, with a cutoff value of 91.2 pg/ml for prediction of risk of vascular diabetic complications 30) .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The results showed that the mean IL-34 levels in GCF (969.44±143.27 pg/ml) and plasma (774.02±215.47) were increased in patients who were obese and had periodontitis (Group IV) compared to in the other groups, and this difference was statistically significant (p<0.001). Chang et al also found IL-34 expression in human adipose tissue, and the circulating concentration was significantly elevated in obese patients and was associated with insulin resistance 7) . Zorena et al concluded that IL-34 could serve as an additional potential inflammatory biomarker, with a cutoff value of 91.2 pg/ml for prediction of risk of vascular diabetic complications 30) .…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, IL-34 is expressed in human adipose tissue. The circulating concentration is significantly elevated in obese patients and is associated with insulin resistance 7) .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that obesity, insulin resistance and endothelial cell damage leading to atherosclerosis are related to adipose tissue dysfunction and ensuing low level inflammation (Lyon and Hsueh, 2003; Shoelson et al, 2006; Howell and Mangum, 2011; Kim et al, 2012; Chang et al, 2014; Dalmas et al, 2014; Fabrizi et al, 2014; Lee et al, 2014a). Increases in levels of pro-inflammatory mediators such as interleukin-6, tumor necrosis factor-alpha and the adipokines, resistin and leptin, are thought to lead to this subacute inflammatory state (Shoelson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that interleukin‐34 (IL‐34) and YKL‐40 are associated with hepatic fibrosis in patients with non‐alcoholic fatty liver disease (NAFLD), which is one of the major etiologies of non‐viral HCC. Interleukin‐34, a fibroblast‐derived cytokine, promotes collagen synthesis by hepatic stellate cells, and elevated serum IL‐34 levels are found in patients with chronic inflammation, including obesity, and insulin resistance . Interleukin‐34 is also involved in the differentiation and survival of macrophages in response to inflammation .…”
Section: Introductionmentioning
confidence: 99%